EXTENT OF ADOPTION OF ELECTRONIC RECORDS PROCESSING PRACTICES IN POLYTECHNICS IN EDO AND DELTA STATES (NAU Journal of Technology and Vocational Education, 2024)
Nigerian tertiary institutions seem to have embraced electronic record-keeping procedures in orderto make records available at the right time and at the right place butthe extent to which secretaries ofpolytechnics in Edo and Delta States have adopted electronic record processing practices is notempirically known. In order to execute this study, one research question was raisedand twohull hypotheses were tested at 0.05 level of significance. The study adopted the descriptivesurvey design. Populationof 188 secretaries in polytechnics in the two states were used for thestudy without sampling and the size was not too large. A validated questionnaire by experts wasused for data collection.Cronbach alpha method was used to establish the reliability of theinstrument which yielded coefficients of 0.75. Mean and standard deviation were used to answerthe research question and determine the homogeneity of respondents’ means while t-test wasused to test the hypotheses at 0.05 level of significance. The findings of the study revealed thatelectronic records processingpractices were adopted in managing records in polytechnics inEdo and Delta States to a high extent. The findings also revealed that secretaries do not differsignificantly in their mean ratings on their extent of adoption ofelectronic records processingpractices in managing records in their institutions as a result of gender and years of workingexperience. The study concluded that secretaries in polytechnics in Edo and Delta States needfurther retraining exercises to enable them acquire new digital skills that will facilitate the art ofutilizing modern electronic records processing activities for effective and efficient managementof records. It was recommended among others that polytechnics should ensure that adequate,functional and modern facilities are available for secretaries and administrative staffs to enablethem perform electronic record processing practices effectively and efficiently.
Keywords: Records, record management, electronic records processing practices